Examining offense timing among the top four teams, in the 2022 men's Eurobasket tournament - Lemondidis, N.; Vasilakis, S.; Lemonidou, E. (Journal of Physical Education and Sport, 2024)
The timing of offensive maneuvers in basketball plays is crucial role in shaping game outcomes. Equally critical is the manner in which offenses are executed and by whom. This study aimed to analyze the offensive strategies, employed by the top four teams in the men's Eurobasket 2022 tournament (Spain, France, Germany, and Poland), as well as those of their opponents, in order to identify any differences in timing and execution. Thirty one games were recorded, the 24-second shot clock was divided into four parts, and 12 different ways of attacking were observed for each team. The positions of the players executing these offenses were also recorded. For the statistical analysis, the independence of values was assessed using the non-parametric x² (chi-square) distribution in the PSPP 1.6.0 statistical package. The reliability of the observations was determined using the statistical index kappa (k) (Cohen, 1960). The results revealed statistically significant differences in Spanish team's offensive tactics, whose dominant strategy was pick and roll, (31.5%) while the other teams used one on one attacks, (30.2%) out of their total attacks. There were also significant differences in the timing of attacks. The Spanish team made longer attacks (19'' to 24'') in 26.6% of their total attacks, while the corresponding percentage of the other teams was 20.6%. Furthermore, a significant difference was found in the attacks executed by Spain's big men, with 22.3% of their attacks, while in the other teams the percentage was 16.8%. The results of this study may give coaches important information regarding offensive strategy in basketball games and players can use this knowledge to increase their performance.